2015
DOI: 10.1017/ipm.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

‘Codeine is my companion’: misuse and dependence on codeine containing medicines in Ireland

Abstract: Objectives. Global concern around over the counter availability of codeine containing products and risk of misuse, dependence and related harms are evident. A phenomenological study of lived experiences of codeine misuse and dependence was undertaken in Ireland, following the Pharmaceutical Society of Ireland's 2010 guidelines for restricted supply of non-prescription codeine containing products.Methods. In-depth interviews were conducted with a purposive sample of adult codeine misusers and dependents (n = 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 58 publications
6
65
0
Order By: Relevance
“…Previous research suggests that codeine administration for emotional distress may be a good indicator for dependence or risk of developing dependence. 29 GPs and pharmacists need to be vigilant of reasons for use when deciding to prescribe or sell codeine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that codeine administration for emotional distress may be a good indicator for dependence or risk of developing dependence. 29 GPs and pharmacists need to be vigilant of reasons for use when deciding to prescribe or sell codeine.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Most people were reluctant to spend time travelling on costly public transport, and people were also reluctant to pay for treatment, as they were often aware that there were government-funded centres available -albeit with a lengthy waiting list. [14] Surprisingly, only 10% of our SA participants indicated that the geographical location of treatment settings would be a problem, compared with 22% for Ireland, and none mentioned transport-related costs as being a barrier for codeine patients in SA, compared with 30% for Ireland. [16] Practitioners were optimistic about preventing relapse by the use of alternative non-opioid pain relief in patients with coexisting pain and addiction to codeine medicines.…”
Section: Discussionmentioning
confidence: 87%
“…[13] Qualitative research recently conducted in SA and Ireland furthermore underscores the lack of awareness of risk around habitforming use of medicines containing codeine and pathways towards dependence in patients who attended treatment. [14,15] Stigma was listed as less of a problem in SA compared with data obtained from the UK and Ireland as part of the CODEMISUSED project, [16] but in SA and Ireland child-care issues were raised more frequently than in the UK. Six out of 10 addiction treatment providers surveyed in SA indicated that affordability of services would be a barrier to codeine patients accessing treatment, compared with only 22% in Ireland and none in the UK, where there is a National Health Insurance system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggests that individuals who continue to misuse or are dependent on codeine containing medicines intentionally bypass 'real time monitoring' practices and engage communication strategies centred on manipulation and deceitfulness either when negotiating scripts from their doctor or purchasing their medicines. Managing such behaviours require further advanced communications training for medical and pharmacy practitioners, particularly in the area of interpersonal communication strategies with a specific focus on motivational interviewing and brief interventions (44,45).…”
Section: Discussionmentioning
confidence: 99%